Reducing sexual violence through safe sanitation?. (18th October 2022) - Ray, Isha
Abstract: Reliable access to safe sanitation is a cornerstone of human health and gender equality. Over the last 10 years, the risks of sexual violence and sexual harassment (SVSH) associated with inadequate access to household latrines have received considerable attention. This is especially true of studies on seeking sanitation under cover of darkness. Here I examine the evidentiary basis of claims that incidences of SVSH can be reduced with better access to latrines. I focus on SVSH towards women and girls, though all genders can face sexual violence. I argue that promoting household (or on premises) latrines as a protection against sexual violence cements entrenched biases about 'good' girls, 'true' rape, and the place of women in public spaces. Thus, arguments claiming that latrine construction is an important tool against SVSH, while gender-sensitive in intent, can be misogynistic in impact. HIGHLIGHTS: Researchers have argued that sexual violence and harassment can be reduced by constructing more household toilets. This argument inadvertently supports rationales for keeping women away from public spaces. Promoting latrine construction as a way to prevent rapes also perpetuates gender-biased myths related to 'true' victims and 'good' versus 'bad' girls. This form of sanitation advocacy can become misogynistic.